The Impact of Probiotic Supplementation on Cognitive, Pathological and Metabolic Markers in a Transgenic Mouse Model of Alzheimer’s Disease - Webberley, Thomas S.; Masetti, Giulia; Bevan, Ryan J.; Kerry-Smith, Joshua; Jack, Alison A.; Michael, Daryn R.; Thomas, Sophie; Glymenaki, Maria; Li, Jia; McDonald, Julie A. K.; John, Daniel; Morgan, James E.; et al. (Frontiers in Neuroscience, 2022)
Brain degenerative disorders such as Alzheimer’s disease (AD) can be exacerbated by aberrant metabolism. Supplementation with probiotic bacteria is emerging as a promising preventative strategy for both neurodegeneration and metabolic syndrome. In this study, we assess the impact of the Lab4b probiotic consortium on (i) cognitive and pathological markers of AD progression and (ii) metabolic status in 3xTg-AD mice subjected to metabolic challenge with a high fat diet. The group receiving the probiotic performed better in the novel object recognition test and displayed higher hippocampal neuronal spine density than the control group at the end of the 12 weeks intervention period. These changes were accompanied by differences in localised (brain) and systemic anti-inflammatory responses that favoured the Probiotic group together with the prevention of diet induced weight gain and hypercholesterolaemia and the modulation of liver function. Compositional differences between the faecal microbiotas of the study groups included a lower Firmicutes:Bacteroidetes ratio and less numbers of viable yeast in the Probiotic group compared to the Control. The results illustrate the potential of the Lab4b probiotic as a neuroprotective agent and encourage further studies with human participants.